The effect of board of directors’ characteristics on disclosing tone in the annual reports: evidence from Amman stock exchange - Salah Kayed; Abdulhadi H. Ramadan; Amer Morshed; Hashem Alshurafat; Roaa Al-Zyoudi (Discover Sustainability, 2024)
Abstract Purpose This study examines the impact of board characteristics (i.e., board independence, board size, number of board meetings, foreign directors, and representation of females on the board of directors) on the tone disclosed in the banks’ annual reports of the Jordanian banking industry. Design/methodology/approach The sample of this study contains all banks in the Jordanian banking industry for the period 2010–2019. This study employs a quantitative research method to examine the impact of the board of directors' characteristics on the tone of disclosure. Although disclosure tone is qualitative information, it has been converted into numbers (the frequency of positive and negative words) using the NVivo program. The "tone" is measured in this study based on lists of positive and negative words developed by Loughran and McDonald’s list. Then, a pooled regression analysis is used to investigate whether the board of directors' characteristics affect the disclosure tone. Findings The study results show that corporate governance plays a significant role in disclosing tone in banks’ annual reports. Clearly, the results show that the number of board meetings positively impacts the emergence of tone disclosure. In addition, the presence of women on the board of directors positively impacts the tone disclosure. In contrast, the foreign directors’ existence on the board of directors has a negative effect on the tone disclosure. However, the results show no relationship between board independence, size, and tone disclosure. Originality/value This study contributes by providing knowledge and insights into tone disclosure in an emerging market. Based on signaling theory, tone disclosures are the mangers’ signals given to the stakeholders in their firms’ financial reports. Managers disclosing positive tones to convey good news to their stockholders, and this considered as one of the main targets for these managers. This study provides insights into the relatively under-researched area of disclosure tone in an emerging market. It sheds light critically on how board of directors’ characteristics within the banking industry in Jordan contributes to their disclosure tone in the annual reports. This contribution helps stakeholders including policymakers, CEOs, and capital market participants understand how board members’ characteristics can contribute in building a straightforward disclosure tone in their financial reports. The study's conclusions are particularly significant because they attest to the need for financial knowledge and diversity of gender. The tone disclosure presented in financial reports, along with its anticipated impact on future investor decisions, is a crucial aspect for stakeholders to comprehend. Practical implications Our findings suggest that banks in Jordan should carefully consider the characteristics of their boards of directors, as these are crucial to ensuring transparency in disclosures. Additionally, maintaining a consistent and clear tone in annual reports is vital, as it significantly influences investor confidence and interest. This transparency can be strengthened by the quality and effectiveness of the bank's directors. Recommendations/future research For future research, the current study results can be reinvestigated to other emerging countries, other sectors, other measures for the disclosure tone and the board of directors’ characteristics, and more important different periods to include the effects of COVID-19 pandemic and financial crisis.